1993
DOI: 10.1111/j.1432-1033.1993.tb17661.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction potentials and their pH dependence in site‐directed‐mutant forms of azurin from Pseudomonas aeruginosa

Abstract: A spectroelectrochemical method has been used to determine the reduction potential of the copper site in wild-type and 22 mutant forms of azurin from Pseudomonas aeruginosa at 25 "C and in the range pH 4-8; the effect of buffers and ionic strength on the potentials has also been studied. Amino-acid residues changed include Metl21, which provides an S atom at a distance of about 0.3 nm from the metal, some amino acids in the hydrophobic patch, other residues believed to be important in electron transfer with ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
164
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(180 citation statements)
references
References 32 publications
16
164
0
Order By: Relevance
“…It also supports the conclusion above that a water molecule is not embedded in the cavity. A polarizable water molecule close to the copper ion would lower the potential, as in the mutant where a stop codon was introduced in position 121 (Pascher et al, 1993). This leads to an open structure allowing water entry which results in a reduction potential reduced by over one third (from 310 to 205 mV).…”
Section: Cys112mentioning
confidence: 99%
“…It also supports the conclusion above that a water molecule is not embedded in the cavity. A polarizable water molecule close to the copper ion would lower the potential, as in the mutant where a stop codon was introduced in position 121 (Pascher et al, 1993). This leads to an open structure allowing water entry which results in a reduction potential reduced by over one third (from 310 to 205 mV).…”
Section: Cys112mentioning
confidence: 99%
“…Since the optical spectra of all the mutated azurins were principally similar, although small differences in the spectral parameters were observed, we concluded that the environment around type 1 copper is not greatly altered by the mutations. Differences of + 3 nm in maximum absorption are commonly seen for azurin mutants of surface residues [21]. Redox potentials of wild-type and mutated azurins were determined by redox titration in 0.1 M potassium phosphate buffer at pH 7.0.…”
Section: Site-directed Mutagenesis and Physicochemical Measurements Omentioning
confidence: 99%
“…Replacement of Met"' in the azurins tunes the EO over a range of -105 mV to +138 mV with respect to the wt value at pH 7.0 [21,69]. Replacing His1i7 or His46 in the azurins by a glycine and supplying the Cu site with external ligands can increase the midpoint potential by about 100 mV [57].…”
Section: Midpoint Potentialsmentioning
confidence: 99%
“…Replacements in the second coordination sphere of the Cu can have fairly drastic affects on E,,, the causes of which are not clearly understood. For instance, the Pro*'Ala mutation in pseudoazurin causes a change of + 139 mV of E. [68], while the Asn47Leu and Asn47Asp mutations in azurin cause changes by + 110 and +23 mV, respectively [67,69]. Study of the temperature dependence of the Asn47Leu mutant vs. the wt, moreover has shown that the observed AE, between wt and mutant can strongly vary with temperature due to a sizeable entropy contribution to the difference in E, [67].…”
Section: Midpoint Potentialsmentioning
confidence: 99%